Targeting the bacterial SOS response for new antimicrobial agents: drug targets, molecular mechanisms and inhibitors - Lanyon-Hogg, T (Future Science, 2021)
Antimicrobial resistance is a pressing threat to global health, with multidrug-resistant pathogens becoming increasingly prevalent. The bacterial SOS pathway functions in response to DNA damage that occurs during infection, initiating several pro-survival and resistance mechanisms, such as DNA repair and hypermutation. This makes SOS pathway components potential targets that may combat drug-resistant pathogens and decrease resistance emergence. This review discusses the mechanism of the SOS pathway; the structure and function of potential targets AddAB, RecBCD, RecA and LexA; and efforts to develop selective small-molecule inhibitors of these proteins. These inhibitors may serve as valuable tools for target validation and provide the foundations for desperately needed novel antibacterial therapeutics.